PERMOHONAN EKSEKUSI KEPADA PENGADILAN NEGERI BERKAITAN DENGAN PERJANJIAN FIDUSIA TERHADAP JAMINAN YANG DIGELAPKAN - Setia Budi (JCH (Jurnal Cendekia Hukum), 2017)
The execution of fiduciary guarantee execution is stipulated in Article 29 of Law Number 42 Year 1999 concerning Fiduciary Guaranty which states that execution of fiduciary guarantee execution can be done by executing executorial title, sale by public auction, or sale under the hand with agreement of both parties, but in practice sometimes found when executing fiduciary guarantees on one of its borrowers, the guarantee has been transferred and controlled by a third party without the consent of the creditor. Therefore, this paper aims to find out how the process of fiduciary fraud execution against bad debts and how the legal protection against the creditors in the credit agreement of the bank against the problem digelapkannya fidusia guarantee by the debtor party.